An investigation uncovering how students and how tutors design learning objects for novice students to use when acquiring established resuscitation knowledge - Williams, Alan R. (2018)
Higher education in the twenty-first century is experiencing transformational change due to the advances in technology, with this period referred to as the Fourth Industrial Revolution – the Information Age. Just as the three previous revolutions created step changes in society so will this one, and as the changes now are occurring over a much shorter time period academics, educators and universities have less time to understand and respond to these events. The three key technological changes are firstly the availability, power and pervasiveness of computers, secondly the development of the Internet and finally how these factors have affected knowledge and learning, in the new millennium.